1, 2, 3 strikes you're out (of blood pressure control). Issue 7 (July 2016) - Langner, Shannon; Lyon, Corey
Abstract : N/A: Sharman JE, Blizzard L, Kosmala W, Nelson MR. Pragmatic method using blood pressure diaries to assess blood pressure control. Ann Fam Med . 2016; 14(1):63–69.